2005
DOI: 10.1016/j.gca.2005.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Natural speciation of Mn, Ni, and Zn at the micrometer scale in a clayey paddy soil using X-ray fluorescence, absorption, and diffraction

Abstract: The natural speciation of Mn (0.19 g/kg), Ni (46 mg/kg) and Zn (42 mg/kg) in the argillic horizon (120 cm depth, pH = 5.6) of an Ultisol from a paddy soil in northern Taiwan was investigated by advanced X-ray synchrotron techniques. Microchemical associations were imaged by synchrotron-based X-ray microfluorescence, host minerals were identified by standard and micrometer-resolved X-ray diffraction, and the local coordination environment of Mn, Ni, and Zn was probed using extended X-ray absorption fine structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 84 publications
(114 reference statements)
7
93
0
Order By: Relevance
“…Mancheau et al [26] found that Zn In acidic to near-neutral aluminium-rich clayey paddy soils in Vietnam was predominantly bound to the hydroxyl-Al interlayers in the fine soil matrix. Similarly, paddy soils in the Kedah plain were sbundant in phyllosilicate minerals in the clay fractions such as kaolinite, smectite and mica [21], which in turn provide a good binder for Zn accumulation.…”
Section: Zn In the Soil Fractionsmentioning
confidence: 99%
“…Mancheau et al [26] found that Zn In acidic to near-neutral aluminium-rich clayey paddy soils in Vietnam was predominantly bound to the hydroxyl-Al interlayers in the fine soil matrix. Similarly, paddy soils in the Kedah plain were sbundant in phyllosilicate minerals in the clay fractions such as kaolinite, smectite and mica [21], which in turn provide a good binder for Zn accumulation.…”
Section: Zn In the Soil Fractionsmentioning
confidence: 99%
“…8). The variation in height of these specific features originates in the planarity of the manganese oxide layer; tall narrow peaks at these positions are characteristic of Mn oxides with undistorted hexagonal layer symmetry and low Mn(III) content (Manceau et al, 2002(Manceau et al, , 2005Webb et al, 2005b). These features arise from Mn-Mn-Mn multiple scattering, which dies away quickly as the Mn-Mn-Mn (i.e., linear adjacent Mn neighbors) angle bends away from 180°.…”
Section: Exafsmentioning
confidence: 99%
“…Natural marine and soil Mn oxides frequently have been reported to be poorly crystalline and to exhibit layer structures (Post, 1999;Manceau et al, 2005;Bodei et al, 2007). It is likely that such morphologies implicate biogenic origin.…”
Section: Comparison To Laboratory Bacteriogenic Mn Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron-based XRF allows the establishment of elemental mappings of small-scale samples, with lateral resolutions in the µm range [34]. By combining different synchrotron X-ray techniques, such as X-ray diffraction, X-ray absorption fi ne-structure analysis (XAFS), and X-ray absorption near edge structure analysis (XANES), information on the mineral phase, the oxidation state and the nearest neighbour atom can be obtained [35][36][37].…”
Section: Measurement Of Nickel In Environmental Samplesmentioning
confidence: 99%